Identification of Predominant Lactic Acid Bacteria and Yeasts of Turkish Sourdoughs and Selection of Starter Cultures for Liquid Sourdough Production Using Different Flours and Dough Yields - Yağmur Gülten; Tanguler Hasan; Leventdurur Sezgi; Elmacı Simel Bağder; Turhan Emel Ünal; Francesca Nicola; Settanni Luca; Moschetti Giancarlo; Erten Hüseyin (Polish Journal of Food and Nutrition Sciences)
Eight samples of mature sourdough were collected from five provinces of Turkey. Lactic acid bacteria and yeasts were isolated and identified and used in different combinations to produce liquid sourdoughs. Microbiological and physicochemical characteristics of the experimental sourdoughs made with different flour types and dough yields were studied. The main lactic acid bacteria species identified were Lactobacillus (L.) sanfranciscensis, Pediococcus pentosaceus, L. plantarum, L. namurencis, L. rossiae, Leuconostoc mesenteroides and L. zymae. L. spicheri, L. paralimentarius, L. mindensis, L. farciminis, L. acetotolerans, L. casei, Enterococcus faecium and Enterococcus durans were also found in sourdoughs at subdominant levels. Among yeasts, mainly Saccharomyces cerevisiae, but also Pichia guiliermondii and Torulaspora delbrueckii were the predominant species of yeasts identified in sourdoughs.